Flipped Classroom Learning Design using Si Raca App: How is Students' Reading Skill? - Hasanudin, Cahyo; Fitrianingsih, Ayu; Fitriyana, Nofia; Priyantoko, P; Setiawan, Dwi (Proceedings International Conference on Education Innovation and Social Science, 2023)
Early reading is the main way of knowledge for primary school students. Therefore, students have to be provided various reading materials which are available and make them feel comfortable in learning to read. The aims of this study are 1) to investigate flipped classroom learning design using Si Raca App in the early reading at primary school; 2) to investigate students’ reading improvements when it has been implemented. This study implements qualitative research in form of classroom action research. The research subjects are first grade students with total of 36 students. This study had been conducted in the even semester of 2022-2023 at MI Muhammadiyah 22 Sugihwaras, Bojonegoro, Indonesia. Research instruments are in forms of reading test questions. Data is collected using test method. It is analyzed using descriptive comparative technique and critical analysis technique. This study concludes that first, flipped classroom using Si Raca App is designed by collaborating flipped classroom model and Si Raca App. This design is implemented in treatments of cycle 1 and cycle 2. It is started from students’ and teacher’s activities before learning, whilst learning, and after learning. Second, there is an improvement in the percentage of completeness in early reading of primary school students. It can be viewed from the completeness percentage in cycle 1 is 77,77%. In cycle 2, it is 91,66%. It means that the classical completeness has been fulfilled in cycle 2.